4-Oxooctahydroquinoline-1(2H)-carboxamides as hepatitis B virus (HBV) capsid core protein assembly modulators. (15th February 2022) - Hwang, Nicky; Ban, Haiqun; Wu, Shuo; McGuire, Kelly; Hernandez, Ellen; Chen, Junjun; Zhao, Qiong; Suresh, Manasa; Blass, Benjamin; Viswanathan, Usha; Kulp, John; Chang, Jinhong; et al.
Graphic abstract: Abstract: Hepatitis B virus (HBV) core protein, the building block of the HBV capsid, plays multiple roles in viral replication, and is an attractive target for development of antiviral agents with a new mechanism of action. In addition to the heteroaryldihydropyrimidines (HAPs), sulfamoylbenzamides (SBAs), dibenzothiazepine derivatives (DBTs), and sulfamoylpyrrolamides (SPAs) that inhibit HBV replication by modulation of viral capsid assembly and are currently under clinical trials for the treatment of chronic hepatitis B (CHB), other chemical structures with activity to modulate HBV capsid assembly have also been explored. Here we describe our continued optimization of a benzamide originating from our high throughput screening. A new bicyclic carboxamide lead featuring an electron deficient non-planar core structure was discovered. Evaluations of its ADMET (absorption, distribution, metabolism, excretion and toxicity) and pharmacokinetic (PK) profiles demonstrate improved metabolic stability and good bioavailability.